Sense of Humor in Student Task Discussion During Covid-19 Pandemic, Is It Important? - Fetri Charisma Mahardika; Dimas Teguh Prasetyo (UM Purwokerto Press, 2021)
The government has established a Study-From-Home (SFH) program to prevent the spread of Covid-19. Implementing the SFH program is an alternative for students to continue to carry out online learning as a substitute for face-to-face meetings. Online task discussion through WhatsApp groups is a solution for completing common tasks which are considered quite effective. However, learning tasks during a pandemic were considered quite burdensome, such as increased stress levels. Previous studies show that increased stress and anxiety during SFH can be reduced through humor. This study conducts an argumentative literature review to determine the importance of humor in students learning during the covid-19 pandemic. This paper shows that humor in the task discussions has an essential role during the Covid-19 pandemic. With humor, it is expected that the level of students’ anxiety during the SFH program decreases. It is also expected to have a positive impact on the effectiveness of group communication in task discussions.